Male-Female Pay Inequity and Public Policy in Canada and the U.S. - Agarwal, Naresh c. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This paper provides a detailed review of the empirical studies that have attempted to disaggregate the observed earnings differentials between men and women into discriminatory and non-discriminatory components. It also examines the existing public policy on equal pay including the equal value/comparable worth concept. A U.S.-Canada perspective is used to see if the two countries have dealt differently with the problem they commonly face.